2020
DOI: 10.3390/min10040326
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Precise Survey Techniques to Find the Connection between Discontinuities and Surface Morphologic Features in the Laže Quarry in Slovenia

Abstract: This paper addresses a stability evaluation of artificial slopes in a quarry located in Slovenia that was affected by a rockslide in March 2019. In order to ensure the safety of further production, measures were taken to restore the slopes. A stability assessment of the remaining parts of the quarry was conducted. To ensure quality spatial data, an upgraded study based on terrain mapping and aerial photogrammetric imaging using an unmanned aircraft was carried out, in addition to a traditional field survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Research has shown that in the rainfall seepage process, the rock and soil mass bulk density and the pore water pressure increase, the sliding force of the slope body increases, and the shear strength decreases, resulting in slope failure [5,6]. Cracks and weak planes formed during rainfall and seepage are the main geological disaster sources driving slope failure [7,8]. Determination of the geological conditions and change trends of the slope structure, lithology, crack development, water content and weak planes is essential for effective slope disaster prediction and forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that in the rainfall seepage process, the rock and soil mass bulk density and the pore water pressure increase, the sliding force of the slope body increases, and the shear strength decreases, resulting in slope failure [5,6]. Cracks and weak planes formed during rainfall and seepage are the main geological disaster sources driving slope failure [7,8]. Determination of the geological conditions and change trends of the slope structure, lithology, crack development, water content and weak planes is essential for effective slope disaster prediction and forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…Rockfall is a type of landslide that occurs at a high-speed rate (Hungr et al 2014). Studies on the potential of rockfall at former quarry areas have been extensively conducted in previous studies (Kalpakci et al 2018;Robiati et al 2019;Lazar et al 2020). The assessment of rockfall potential is critical to facilitate the determination of mitigation methods that can be used to reduce the impact.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization in practical applications to daily problems in mining industry is nowadays very common (Török et al 2020;Duarte et al 2020;Lazar et al 2020).…”
Section: Introductionmentioning
confidence: 99%